Pink esthetics in periodontics - Gingival depigmentation: A case series - Arthiie Thangavelu; Sugumari Elavarasu; Piranitha Jayapalan (Wolters Kluwer Medknow Publications, 2012)
Smile expresses a feeling of joy, success, sensuality, affection, and courtesy, and reveals self-confidence and kindness. The harmony of the smile is determined not only by the shape, the position, and the color of the teeth, but also by the gingival tissues. Although melanin pigmentation of the gingiva is completely benign and does not present a medical problem, complaints of "black gums" are common, particularly in patients having a very high smile line. Thus, perio-esthetic treatment modalities strive to achieve a harmonious inter-relationship of the pink with white, which is imperative of all treatment procedures. For depigmentation of gingival, different treatment modalities have been reported, such as bur abrasion, scraping, partial thickness flap, cryotherapy, electrosurgery, and laser. In the present case series, scraping, electrosurgery, and diode laser have been tried for depigmentation, which are simple, effective, and yield good results, along with good patient satisfaction.